18th International Parallel and Distributed Processing Symposium, 2004. Proceedings.
DOI: 10.1109/ipdps.2004.1303205
|View full text |Cite
|
Sign up to set email alerts
|

A hypergraph model for the yeast protein complex network

Abstract: We consider a hypergraph model for the protein complex network obtained from a large-scale experimental study to characterize the proteome of the yeast. Our model views the yeast proteome as a hypergraph, with the proteins corresponding to vertices and the complexes corresponding to hyperedges. Previous work has modeled the protein complex data as a protein-protein interaction graph or as a complex intersection graph; both models lose information and require more space. Our results show that the yeast protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…For instance, it has been found that the proteomic network of yeast forms a hypergraph with the proteins corresponding to vertices and the protein-complexes corresponding to hyperedges [13]. Other large metabolic networks like the one of E. coli have also been found to possess a small-world structure and as most of the reactions of metabolism are multimolecular they can be represented by hypergraphs [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that the proteomic network of yeast forms a hypergraph with the proteins corresponding to vertices and the protein-complexes corresponding to hyperedges [13]. Other large metabolic networks like the one of E. coli have also been found to possess a small-world structure and as most of the reactions of metabolism are multimolecular they can be represented by hypergraphs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other HCPIN proteins that are not included in the KEGG pathways but interact with these pathway proteins are called interaction proteins. The representation of protein complexes using a binary protein-protein interaction graph remains a challenge because without detailed structural studies it is often not possible to distinguish direct physical interactions from interactions mediated through the complex (49,50). We used triangular pseudonodes, which link proteins involved in the same complex, to represent multiprotein complexes (50).…”
Section: Human Cancer Pathway Protein Interaction Networkmentioning
confidence: 99%
“…We have extended the concept of a k-core to a hypergraph in earlier work [19]. k-cores have been used earlier for clustering proteomic networks as a way of identifying highly connected subnetworks and for removing proteins belonging to low shell values [4].…”
Section: K-cores and K-shells In Graphsmentioning
confidence: 99%